Effect of Supplemented Sucrose and Injected Insulin Under Different Recovery Time on Glucose, Fructose and Ribose Meat Lamb - Elis Dihansih; Eddie Gurnadi; C. Hanny Wijaya; Rudy Priyanto (Indonesian Journal of Applied Research (IJAR), 2020)
An experiment was conducted in order to study the influence of supplemented sucrose and injected insulin under different recovery times following transportation on lamb flavor quality. For the purpose the study used fifty four female local lamb (10 to 12 months of age) with weight ranging from 14 to 17 kg. The experimental lamb were assigned into a completely randomized design with 2x3x3 factorial arrangement with 3 replications. The first factor was sucrose supplementation with 2 levels (0 and 6 g/kg body weight). The second factor was insulin injection after transportation with 3 levels (0, 0,3 and 0,6 IU). The third factor was the duration of recovery times with 3 levels (2, 4 and 6 h prior to slaughtering). Parameters measured were glucose, fructose, and ribose. Results showed that feeding sugar and injecting insulin to lamb following transportation increased glucose, fructose, and ribose content of raw meat while recovery time was not affect meat sugar content. Interaction was not occur between treatment of Sugar, insulin, and recovery time.